Aminoglycoside induced ototoxicity risk in the cystic fibrosis population: The utility of large‐scale screening. Issue 3 (20th December 2022) - Lopes, Jaime; Vidal‐Folch, Noemi; Lundquist, Patrick; Schimmenti, Lisa A.; Demirel, Nadir; Dean, Vicki; Olson, Janelle; Auth, Tom; Butz, Malinda; Reed, Katelyn; Wylam, Mark; Balcom, Jessica; et al.
Abstract: Background: MT‐RNR1 variants are a well‐known cause of aminoglycoside‐induced hearing loss (AIHL). Individuals with cystic fibrosis (CF) routinely receive aminoglycosides and are at high risk of AIHL. However, genetic testing before treatment is not routinely performed due to perceived rarity of risk, and cost ineffectiveness with traditional technologies. Aim: Assess the utility of large‐scale screening for AIHL risk in the CF population, using digital droplet polymerase chain reaction (ddPCR), a novel and scalable low‐cost molecular technique. Methods: Using a clinically validated ddPCR assay, we performed retrospective testing on 122 and prospective testing on 32 individuals with CF for the two most common pathogenic variants associated with AIHL, MT‐RNR1 m.1555 A > G and m.1494 C > T. Our study screened the largest known cohort of pediatric cases of CF (94/154) for these specific alterations. Results: We identified two individuals positive for MT‐RNR1 m.1555 A > G and no positives for m.1494 C > T. Of 32 prospective cases, 17 had aminoglycoside exposure. The positive case in our prospective group recently began inhaled tobramycin and denied hearing issues. The clinician adjusted to care for both the patient and sibling with CF (not included in cohort) who is presumed positive for m.1555 A > G due to the nature of mitochondrial inheritance. Conclusion: Our findings demonstrate the utility of pretreatment screening in the cystic fibrosis population for AIHL risk using ddPCR, a scalable and robust testing methodology at a fraction of the cost as compared to other sequencing‐based methods. Therefore, the use of large‐scale screening for AIHL risk in the cystic fibrosis community should be re‐visited.